Taiwan's Democracy under threat [videorecording] - Ministry of Foreign Affairs, Republic of China (Taiwan) (Taipei, Taiwan Ministry of Foreign Affairs, Republic of China (Taiwan))
Taiwan, also known as Formosa, is home to an abundance of animal and plant life and a diverse ethnic and cultural heritage. This verdant and beautiful island, crossed by the tropic of cancer, is the principle gateway to Asian markets for North American and European business. But over the past 10 years, the Taiwanese have lived under a constant shadow; the threat of 784 Chinese missiles aimed directly at Taiwan.
Donated by Mr. Wellington Wei / Taiwan Economic and Cultural office (10.26.06)
Keywords: Taiwan